At tarbiyyah al khuluqiyyah ‘an Birri al wâlidayni fî Sûrati al ahqâf al âyah 15 - Heru Saiful Anwar; Siti Rahmah Mutazawwidah Bitaqwallah (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2018)
The qur’an is the book guidelines who guide for mankind about affairs belief, and attitude devoted to serve the end and the beginning. Besides in the qur’an have been explained to the law about the manner of qur’an at islamic composed of different sorts command, prohibition, and suggestions or in accordance with matter his discussion, one of them: the orders kind to both parents and obey him and prohibit to disobeyed against them, and in it the qur’an have made the possibility of children being the gem and comfort of hearts, while others an enemy to their parents. This study is used library researc. Meanwhile in the analysis researchers used a method of descriptive analytical method and content analytical method. So the results of the study in verses of the quran is: 1 ) in the form of a Al-Ahqof verse 15 there are education and their offspring and what the remembrance of the home about birrul walidaini, 2 ) remembrance of the home in education about birrul walidaini in the form of a Al-Ahqof verse 15 teach someone to do good to the parents and are subordinating themselves to both of them because the God’s order and not because the order whose home is the fire.